2003
DOI: 10.1016/s0304-4017(03)00064-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of condensed tannins on goats experimentally infected with Haemonchus contortus

Abstract: Although the use of tanniferous plants or condensed tannins as an alternative to anthelmintics to control gastrointestinal nematodes has been largely documented in sheep, studies remain scarce in goats. The objective of this study was therefore to assess the possible impact of condensed tannins in goats infected with adult Haemonchus contortus. Two groups of cull goats were experimentally infected with 10.000 L3 of H. contortus. After 4 weeks, quebracho extracts, representing 5% of the diet DM, were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
2
17

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 23 publications
8
88
2
17
Order By: Relevance
“…In addition, in vivo studies have shown that the administration of quebracho extract, a commercially available extract from Schinopsis spp., reduced faecal egg counts and worm numbers in parasitised sheep (Athanasiadou et al, 2001a;Butter et al, 2001). Similarly, parasitised goats benefited from the inclusion of plant extracts containing high levels of secondary metabolites in their diets (Akhtar and Ahmad, 1992;Paolini et al, 2003a and. In some cases, the antiparasitic efficacy of plant extracts has been similar to that of broad-spectrum anthelmintic drugs; Satrija et al (1994) almost eliminated intestinal nematodes within 7 days of supplementation with papain extract.…”
Section: Studies On the Whole Plant: Strengths And Limitationsmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, in vivo studies have shown that the administration of quebracho extract, a commercially available extract from Schinopsis spp., reduced faecal egg counts and worm numbers in parasitised sheep (Athanasiadou et al, 2001a;Butter et al, 2001). Similarly, parasitised goats benefited from the inclusion of plant extracts containing high levels of secondary metabolites in their diets (Akhtar and Ahmad, 1992;Paolini et al, 2003a and. In some cases, the antiparasitic efficacy of plant extracts has been similar to that of broad-spectrum anthelmintic drugs; Satrija et al (1994) almost eliminated intestinal nematodes within 7 days of supplementation with papain extract.…”
Section: Studies On the Whole Plant: Strengths And Limitationsmentioning
confidence: 91%
“…Alkaloids have also demonstrated strong nematocidal activity towards Strongyloides ratti and S. venezuelensis, two rat nematodes used as models for human nematodes (Satou et al, 2002). The nematocidal activity of tannin extracts has been reported as early as the 1960s (Taylor and Murant, 1966), and more recently evidence on the anthelmintic properties of condensed tannins has been supported by a series of in vitro (Dawson et al, 1999;Athanasiadou et al, 2001a;Molan et al, 2003b;Ademola and Idowu, 2006) and in vivo studies (Athanasiadou et al, 2000;Butter et al, 2001;Paolini et al, 2003a and. However, despite their anthelmintic properties, it is not yet clear whether medicinal plants could actually have a role in controlling parasitism in livestock.…”
Section: Medicinal Plants and Parasitised Hosts: Viewing The Whole Pimentioning
confidence: 93%
See 1 more Smart Citation
“…Initially, animals from GII presented lower reduction, followed by GIII on the end of treatment period, confirming the potential use of taniniferous plants in the nematodes control. Many experiments correlated the CT uses with decrease of female helminthes fecundity (ATHANASIADOU et al, 2000a(ATHANASIADOU et al, , 2001aMIN;HART, 2003;PAOLINI et al, 2003aPAOLINI et al, , 2003b, standing out its importance in nematode epidemiology Despite the lower epg values from animals treated with CT in this study, the number of total worms presented in the intestines of sheep from different treatments was similar (P > 0.05). However, sheep treated twice with AE, which did not present the lower epg, showed a significantly lower number of nematode female.…”
Section: Discussionmentioning
confidence: 43%
“…However, besides its limited usefulness, the use of 4 gm of these wire particles in late pregnancy was reported to threaten the life of multiple born offspring (Burke et al, 2005). On the other hand, plant extracts such as condensed tannins, which are secondary tanniferous plant metabolites, have been found to reduce H. contortus faecal egg counts and the number of eggs per female worm in goats (Paolini et al, 2003) and the faecal egg counts, worm number and fecundity of T. colubriformis in sheep (Athanasiadou et al, 2000). Similarly, flower extracts of Calotropis procera have shown excellent anthelmintic activity against H. contortus in sheep (Iqbal et al, 2005).…”
Section: Other Treatment Methodsmentioning
confidence: 99%